IMPLEMENTASI PROGRAM-PROGRAM PEMBERDAYAAN NELAYAN TRADISIONAL - Jumanah Jumanah; Abdul Aziz; Anti Annisa Subhiyati; Marlina (NIAGARA Scientific Journal, 2022)
This article discusses the Implementation of Fishermen Empowerment Programs which consist of the Training and Guidance Program, the Coastal Community Economic Empowerment Program (PEMP) and the National Marine and Fisheries Independent Community Empowerment Program (PNPM Mandiri-KP), the Revitalization of Ships and Fishing Equipment Programs. Provided by the Government to Fishermen through Group Mechanisms and Capital Assistance Programs, Skills and Knowledge Improvement Programs, and Fisheries Sector Business Diversification Programs, Fisherman Insurance Premium Assistance Programs (BPAN), Fishermen Equipment Assistance Programs, Capture Fisheries Rural Mina Business Development Programs (PUMP) PT). The purpose of this paper is to oversee the programs implemented by the government in an effort to empower traditional fishermen to run effectively and efficiently. The method ofwriting this research is based on the results of research findings from vos viewer regarding the Implementation of Fishermen Empowerment Programs.One of the findings from several researchers that we quote is the Fisherman Insurance Premium Assistance program in collaboration with PT. Jasindo, thepayment of fishermen's insurance premiums is assisted for a year, after which fishermen can continue their policies independently with a small premium of around Rp. 75,000 per year.